Study Of Shape-Based Semi-Local Point Descriptor For Building Recognition - Hashim, Noramiza (2008)
In this thesis project, the author has carried out a study involving low-level features and middle-level features that can be used for man-made object recognition. This study focuses on a very specific type of man-made structure, i.e. buildings, taken from image capturing devices from ground-level.